Translanguaging, Diglossia and Bidialectalism in the Video Gamer Argot (Papers in Arts and Humanities, 2021)
Video games have undergone an extensive technological advancement which has triggered a rapid shift in the role and potency the different media have gained in meeting infotainment needs. The widespread use of the internet has increased the frequency of video gaming among the youth thus promoting the emergence of linguistic material which could be instrumental in second language acquisition. The present paper aims to reveal the linguistic gains from virtual multicultural environments for video gamers in relation to their communication needs, a situation which rightfully characterizes them as bilinguals. Despite the continuing linguistic experimentation activities initiated by researchers, the video gamers’ language utilization has not been paid much attention to as potential research domain in bi/multilingualism. The research has capitalized on the germane information of a cross sectional survey conducted on secondary school video gamer students in Hungary by investigating their language use habits derived from video game usage. The ample research scope results contribute to filling the linguistic gap of word formation methods, translanguaging, diglossia and bidialectalism by comparing the international and Hungarian instances of the video gamer argot. We also journey through the description, modelling, explanation of several processes which could happen within and outside the digital world as an illustration of language use in contact.
Keywords: gamer argot; code -switching; translanguaging; subcultural language development; language change